Jean Lafitte pirate-hero of the war of 1812 - Weintraub, Aileen (New York : Rosen, 2002)
Traces the life of Jean Lafitte, New Orleans privateer and pirate who aided American forces against the British during the Battle of New Orleans.
Includes index.
AR
K-3.
3.
Accelerated Reader
Keywords: Laffite, Jean; Pirates -- Biography; New Orleans (La.), Battle of, 1815.; Privateering -- History